Embracing Augmented Reality and Virtual Reality in South African Basic Education: A Systematic Literature Review - Beauty Mugoniwa (Journal of Information System and Informatics, 2026)
This study reviews the integration of augmented reality (AR) and virtual reality (VR) in South African basic education. To investigate how immersive technologies are applied in teaching and learning, focusing on learner outcomes, teacher preparedness and systemic enabling conditions. The systematic literature review (SLR) was guided by Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) and Systematic Procedures and Rationales for Systematic Literature Reviews (SPAR-4-SLR) frameworks and analysed 22 studies from journal articles, conference papers and theses published between 2018 and 30 September 2025. AR and VR adoption remains uneven and largely experimental, with implementation concentrated in urban and better-resourced facilities, particularly within STEM-related subjects. Browser-based simulations, low-cost virtual laboratories and mobile applications were the most frequently reported technologies, while fully immersive VR deployments were limited due to the financial and infrastructural constraints. Also, immersive technologies can improve experiential learning, conceptual understanding and learner engagement. Adoption is constrained by policy limitations, inadequate infrastructure, unequal access between rural and urban schools and insufficient teacher training. Synthesising fragments evidence and interpreting adoption patterns through the Technology Acceptance Model (TAM), Unified Theory of Acceptance and Use of Technology (UTAUT) and Theory of Planned Behavior (TPB). There is a need for context-sensitive implementation strategies, infrastructural investment and improved teacher development to support AR/VR integration.